2009
DOI: 10.1073/pnas.0909541107
|View full text |Cite
|
Sign up to set email alerts
|

Effective collaboration between marginal metallophilic macrophages and CD8+dendritic cells in the generation of cytotoxic T cells

Abstract: The spleen is the lymphoid organ that induces immune responses toward blood-borne pathogens. Specialized macrophages in the splenic marginal zone are strategically positioned to phagocytose pathogens and cell debris, but are not known to play a role in the activation of T-cell responses. Here we demonstrate that splenic marginal metallophilic macrophages (MMM) are essential for crosspresentation of blood-borne antigens by splenic dendritic cells (DCs). Our data demonstrate that antigens targeted to MMM as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
187
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(200 citation statements)
references
References 29 publications
9
187
0
1
Order By: Relevance
“…10 A recent report suggested that after intravenous immunization with rHuAd5, marginal metallophilic macrophages capture antigen and transfer it to CD8␣ ϩ DCs. 44 Because we observed that most of the antigen within DLNs was located in CD11b ϩ cells (supplemental Figure 1), macrophages in the subcapsular sinus of the LNs may play a similar role after intramuscular rHuAd5 injection. However, our data suggest that this process would only be important for initial priming and not long-term maintenance.…”
Section: Discussionmentioning
confidence: 94%
“…10 A recent report suggested that after intravenous immunization with rHuAd5, marginal metallophilic macrophages capture antigen and transfer it to CD8␣ ϩ DCs. 44 Because we observed that most of the antigen within DLNs was located in CD11b ϩ cells (supplemental Figure 1), macrophages in the subcapsular sinus of the LNs may play a similar role after intramuscular rHuAd5 injection. However, our data suggest that this process would only be important for initial priming and not long-term maintenance.…”
Section: Discussionmentioning
confidence: 94%
“…Both freely draining and APC-associated NPs arrive in the subcapsular sinus of the lymph node. This region is rich in CD169-expressing macrophages [51], which in the spleen are important for the coordination of CD8+ dendritic cells and their stimulation of effective CD4+ and CD8+ T cell responses against invading pathogens [52]. Subcutaneous delivery of NPs is very effective for stimulating immune responses to numerous T and B cell antigens [50,53].…”
Section: Np Administration Route and Organ Localizationmentioning
confidence: 99%
“…CD169 + MZMMFs are known to contribute to cross-presentation of blood-borne Ags by splenic DCs (41). In the LNs, CD169 + cells are found in the sinus and have the ability to cross-present Ags from dead cells (42).…”
Section: Depletion Of a DC Subset That Expresses Xcr1mentioning
confidence: 99%